Unraveling Lifestyle Disease Vulnerabilities among Adolescents: A Comprehensive Comparative Analysis of Private and Government School Students in Rawalpindi and Islamabad - Murtaza, Ghulam; Hamza, Ali; Usama, Muhammad; Noor, Azeema; Naeem, Mahnoor; Javed, Ammara; Hashmi, Syeda Shaheera Riaz; Arshad, Daud; Mustafa, Maria; Arshad, Wajiha; Zahid, Rabia; Bibi, Asma; et al. (International Journal of Health Sciences, 2024)
Purpose: The increasing prevalence of lifestyle diseases in adults necessitates a closer examination of risk factors that manifest during adolescence. This study addresses this imperative, aiming to comprehensively compare lifestyle disease risk factors among adolescents attending private and government schools, with a specific focus on the distinctive nuances present within diverse educational environments. The primary objective of this cross-sectional study is to provide a thorough exploration of lifestyle disease risk factors, thereby contributing to a more nuanced understanding of the complexities inherent in adolescent health within different school settings. The study's aim is to not only identify prevalent risk factors but also to highlight the variations that exist between students in private and government schools. Methodology: The study engaged 600 adolescents from secondary schools in Rawalpindi and Islamabad, with 300 participants from each sector, employing purposive sampling for selection. Beyond the standard measurements of Body Mass Index (BMI), height, and weight, a comprehensive assessment encompassed dietary habits, physical activity levels, screen time, family history of lifestyle diseases, and active/passive smoking. Findings: Noteworthy findings include a substantial 81% of overweight individuals affiliated with private schools, indicating a distinct prevalence in this demographic. Dietary disparities were evident, with private schools displaying a 60% daily consumption of fruits and vegetables, in contrast to 40% in government schools. Further distinctions were observed in daily dairy intake (54% in private schools vs. 46% in government schools) and weekly meat consumption (56% in private schools vs. 44% in government schools). Private schools exhibited higher rates of daily and weekly fast food (54%) and soft drink consumption (67%) compared to government schools (46% and 33%, respectively). Physical activity engagement was reported by 45% of private school students and 55% of government school students, while screen time exceeding 2 hours was reported by 55% of private school students and 45% of government school students. Family history of lifestyle diseases was more significant among government school students. Additionally, 8% of private school students and 7% of government school students reported smoking, with 20% of private school students and 24% of government school students indicating a history of passive smoking. Unique Contribution to Theory, Practice, and Policy: The study enriches theoretical understanding by offering a nuanced exploration of lifestyle disease risks and disparities among adolescents. In practical terms, the findings provide insights for designing targeted interventions tailored to the specific needs of private and government school students, informing health promotion programs and strategies. Policy relevance is emphasized through recommendations for school-specific health policies, considering socioeconomic factors, and advocating for long-term monitoring to facilitate effective public health planning. The identification of nuanced lifestyle disease risks within distinct school environments adds a critical dimension to our understanding of adolescent health and informs future policies and interventions